Plan de sucesión para el servicio nacional de aguas subterráneas, riego y avenamiento. - Ramírez-Calderón, Valeria (Instituto Tecnológico de Costa Rica, 2014)
This project is a Succession Plan developed for the Servicio Nacional de Aguas Subterráneas, Riego y Avenamiento. The plan includes the jobs of the next 45 workers who will obtain the right to retirement in the period 2015 – 2021. The purpose of this document is to identify the most suitable candidates to the job description required, but only taking in count the technical requirements. The research is qualitative type. The interview was used to gather the experts' point of view (future retired people), and know which are the most critical aspects to develop the tasks. But also, the other people of the organization had to fill out a form to update their professional profile. Later, with all that information was rated the candidates, and were identified those who are nearby to the ideal profile. An expert panel was selected to qualify the candidates, in which every aspect had a percentage assigned. At the end, 19 profiles have successors, and the other 6 will be sent to external competition.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014.
Keywords: Competencia; Organización; Perfil profesional; Gerencia; Gestión de la información; Administración